Control in Advanced Biofuels Synthesis via Alcohol Upgrading: Catalyst Selectivity to n‐Butanol, sec‐Butanol or Isobutanol. Issue 3 (13th January 2023) - Wingad, Richard L.; Birch, Laurence; Farndon, Joshua; Lee, Jason; Pellow, Katy J.; Wass, Duncan F.
Abstract: Ruthenium complexes with tetradentate PNNP donor ligands demonstrate a marked change in selectivity compared to analogous bis bidentate PN complexes in Guerbet catalysis, producing mixtures of n ‐butanol (17 %), sec ‐butanol (14 %) and ethyl acetate (66 %) rather than the usual 90 %+ selectivity to n ‐butanol. Tridentate PNP ruthenium complexes such as [Ru(H)(Cl)(CO)(Ph2 PCH2 CH2 NHCH2 CH2 PPh2 )] also produce sec ‐butanol and, in optimized conditions (120 °C, 10 mol% NaOEt base), achieve 71 % selectivity to this butanol isomer. The same tri‐ and tetradentate complexes are efficient catalysts for the conversion of methanol/ethanol mixtures to isobutanol (up to 97 % selectivity). In this way, judicious choice of ligand within this general catalyst family allows selectivity to three butanol isomers of interest as fuel molecules. Abstract : Catalyst Technology for Biofuel Synthesis : Renewing Guerbet chemistry – changes in ligand structure and reaction conditions in ruthenium‐catalyzed alcohol upgrading chemistry switches selectivity between butanol isomers relevant as sustainable fuels.